1991
DOI: 10.1128/jb.173.19.6147-6152.1991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the active center of Bacillus stearothermophilus neopullulanase

Abstract: The active center of the neopullulanase from Bacillus stearothermophilus was analyzed by means of site-directed mutagenesis. The amino acid residues located in the active center of the neopullulanase were tentatively identified according to a molecular model of Taka-amylase A and homology analysis of the amino acid sequences of neopullulanase, Taka-amylase A, and other amylolytic enzymes. When amino acid residues Glu and Asp, corresponding to the putative catalytic sites, were replaced by the oppositely charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Among these is that the difference of specificities toward ␣-(134)-and ␣-(136)-glucosidic linkages is caused solely by the difference in the binding modes of substrate and enzymes. We have obtained strong evidence to prove this, because we have observed that the specificities of neopullulanase toward ␣-(134)-and ␣-(136)-glucosidic linkages can be switched by replacing amino acid residues which might be involved in substrate recognition (19).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Among these is that the difference of specificities toward ␣-(134)-and ␣-(136)-glucosidic linkages is caused solely by the difference in the binding modes of substrate and enzymes. We have obtained strong evidence to prove this, because we have observed that the specificities of neopullulanase toward ␣-(134)-and ␣-(136)-glucosidic linkages can be switched by replacing amino acid residues which might be involved in substrate recognition (19).…”
mentioning
confidence: 86%
“…Neopullulanase catalyzes both hydrolysis and transglycosylation at ␣-(134)-and ␣-(136)-glucosidic linkages by one active center (1,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these pioneering prediction in silico analyses delivered by Birte Svensson and Ann MacGregor [4][5][6][7][8][9] have received special attention. In this regard, also the discovery of neopullulanase by Takashi Kuriki [10,11], as a universal enzyme capable to catalyse all four main reactions characteristic for the family, i.e., hydrolysis and formation by transglycosylation of both a-1,4-and a-1,6-glycosidic linkages [12], deserves to be mentioned.…”
mentioning
confidence: 99%
“…Neopullulanase catalyzes hydrolysis and transglycosylation of 1,4 and 1,6 glycosidic linkages at a single active site. 9) The mode of action on pullulan of CDase from Flavobacterium sp. resulted in the production of a remarkably high amount of a branched tetrasaccharide due to its transglycosylation activity.…”
mentioning
confidence: 99%